(3OQ GdMHH aj JGQjN CYjGf MdHs - (3eMeO Hf EHQGgje Hf jhSa Hf YHO GdQMef GdMdHj, GHf GdMfHdj,J (B1271 (3g` s
(3ChdgG (B:s
(3Ef ddJGQjN LdGdI hTQakG hai Wj efThQ hfKQ efKhQg dWGFakG hWQakG s
(3BNQgG (B:s
(3CHh Gdjef eMeO GdTjN Yaja GdOjf Hf Nda GdMfai JbOe PcQg ai GdeMeOjjf s
(3fSNI NRGFfjI HQSe NRGfI GdaGVd MSjf NhLIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs